Roads to the Sky: Indic Ritual Elements in the Vietnam-China Borderlands and Their Maritime Transmission - David Holm (Religions)
One of the basic features of shamanic rituals cross-culturally in East and Southeast Asia is that the ritual itself is structured as a journey up to the sky, climbing the world mountain or the world tree, or else a journey down to the bottom of the sea and back again. The shamanic retinue is understood to make this journey in person, rather than, as in Daoist ritual, sending divine emissaries up to the highest heavens. The journey is conducted through narrative song and dance, accompanied by strings of bells and lutes. The point of departure is the physical village or village household where the ritual is being conducted, and the journey progresses through a series of well-marked way stations via the temple of the earth god to the higher hills and finally to the villages and markets in the sky, before crossing the heavenly seas and ascending the highest mountain. On the way, demons and other impediments are encountered. The route and way stations vary depending on the purpose of the ritual and the intended divine recipient of offerings and submissions. The present article will explore the route up to the sky and the way stations in more detail, taking a single ritual type as performed by the Pụt and Then ritual practitioners as an example. The Pụt and Then are literate ritual specialists found among the Tày and Nùng peoples in northern Vietnam and southern China, near an area which is known to have been a centre of Brahmanical and Buddhist learning from very early times.